استخدام مواد طبيعية المنشأ لإزالة النفط من سطح المياه (Latakia University Journal -Basic Sciences Series, 2018)
تركزت الدراسة على تحديد زمن الامتصاص الأمثل و السعة الامتصاصية الأعظمية لبعض المواد طبيعية المنشأ إضافة إلى رقائق البولي بروبلين المصنعة، بوجود ثلاثة أنواع من النفط بلزوجات مختلفة. ارتبطت قدرة إزالة النفط من سطح مياه البحر ببنية المادة الماصة وخواص سطحها إضافة إلى كمية وخواص النفط وبشكل خاص لزوجته والتي تعتبر العامل الأكثر أهمية للقدرة الامتصاصية للمواد الماصة. بينت الدراسة أن زيادة زمن الامتصاص لا يؤثر في السعة الامتصاصية للمواد المدروسة بوجود نوعي النفط ذي اللزوجة الضعيفة والمتوسطة (LV و MV)، بينما ازدادت السعة الامتصاصية لهذه المواد عند زيادة زمن الامتصاص إلى 30 دقيقة بوجود النفط العالي اللزوجة  HV. تجاوزت القدرة الامتصاصية لخيوط الذرة الصفراء القدرة الامتصاصية للمواد الطبيعية الأخرى، بينما سجلت رقائق البولي بروبلين أعلى سعة امتصاصية. ازدادت السعة الامتصاصية للمواد المدروسة بشكل عام مع ازدياد لزوجة النفط. تبين هذه النتائج إمكانية استبدال المواد المصنعة المستخدمة لإزالة النفط في سوريا بمواد طبيعية صديقة للبيئة وذات سعة امتصاصية عالية نسبياً. This study focused on determination of optimal sorption time and maximal sorption capacity of some natural oil sorbents as well as polypropylene fiber in presence of three oils of different viscosity. The capacity of oil removal from seawater was related to composition and surface properties as well as to oil amount and oil properties especially, its viscosity. These are the most important factors in the oil sorption of sorbents. Results revealed that extension of sorption time does not influence sorption capacity of the examined sorbents in presence of both oils with low and middle viscosity (LV and MV). Nevertheless, the sorption capacity was increased by extension of sorption time to 30 min. for high viscose oil (HV). The sorption capabilities of silk (maize) exceeded those observed for all of the other natural oil sorbents, while polypropylene fiber showed the highest capacity. Overall, the sorption capacity of the studied sorbents increased with increasing oil viscosity. Results  suggest that substitution of synthetic oil sorbents used in Syria by natural sorbents is possible in oil removal, which have relatively high sorption capacity.